Teach me about liberalism: Constructing social elites and the English divide in the Japanese TV drama, Massan. (August 2021) - Ito, Rika
Abstract: Engaging the fields of discourse analysis and language ideology, this paper examines the construction of elitism (Jaworski and Thurlow, 2009) among the characters in the Nippon Hōsō Kyōkai (NHK) morning drama Massan (September 2014—March 2015). The uneven allocation of English abilities along with other semiotic cues associated with class, gender, and age erases the privileged position that elite men occupy in Japanese society. In doing so, male characters with English abilities are discursively constructed as self-motivated individuals with exceptional qualities. By ignoring their inherited privileges, the drama indexes larger neoliberal discourses that hide the increasing social divide in Japanese society. Such discursive representations of English abilities is highly problematic given NHK's position as Japan's only public broadcasting organization.